2016
DOI: 10.1111/sms.12641
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after hip arthroscopy for femoroacetabular impingement in 289 patients with minimum 2‐year follow‐up

Abstract: Femoroacetabular impingement (FAI) is a common cause of hip pain and dysfunction. The purpose of this study was to report outcome 2 years after the arthroscopic treatment of FAI using validated outcome measurements. Two hundred and eighty-nine patients (males = 190, females = 99) with a mean age of 37 years underwent arthroscopic surgery for FAI. Patients were included consecutively in a hip arthroscopy registry. The cohort was evaluated using online web-based validated health-related patient-reported outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 23 publications
7
58
1
2
Order By: Relevance
“…The values obtained were similar to outcomes after hip arthroscopy for FAI 1,810,33,42 and were expectedly higher for those who returned to sport (see Table 2). The most satisfying correlation was between coping mechanisms and specific patient responses on their individual pathway to return to sport.…”
Section: Discussionsupporting
confidence: 62%
“…The values obtained were similar to outcomes after hip arthroscopy for FAI 1,810,33,42 and were expectedly higher for those who returned to sport (see Table 2). The most satisfying correlation was between coping mechanisms and specific patient responses on their individual pathway to return to sport.…”
Section: Discussionsupporting
confidence: 62%
“…Our two groups appear to be representative with regard to their HAGOS scores when compared to previous research with similar populations [19,24,25].…”
Section: Discussionsupporting
confidence: 57%
“…In the past decade, arthroscopic hip surgery has become the standard surgical therapy for FAI (8,(16)(17)(18)(19). A recent study on arthroscopic treatment of FAI (20) reported that 82% of patients (236 of 289 patients) were satisfied with the surgical result after 2 years.…”
Section: Resultsmentioning
confidence: 99%